MMP-2 and TIMP-2 markers for immunohistochemical study on the prenatal development of the rat's primary visual cortex - Mustafa Mohammed Ibraheem (College of Pharmacy / Mustansiriyah University, 2012)
The objective of this study is to relate the prenatal changes with the spatiotemporal pattern of expression and/or activity of the studied markers. The chemical and molecular determinants of the development will be analyzed in a trial to understand some of the factors controlling these prenatal developmental events. Expression of many genes in various areas of the brain is age and development related and may undergo an irreversible change. Therefore, it is very important to study the normal expression of various proteins in order to delineate their physiological functions. Eighteen embryos were used, six embryos for each embryonic age (E16, E18 and E20), three for studying MMP-2 immunohistochemical marker and other three for studying TIMP-2 immunohistochemical marker. During prenatal cortical development, the reaction of MMP-2 marker was located within the extracellular matrix of the all developing zones. While no activity or reaction of TIMP-2 could be depicted through out the extracellular matrix at any embryonic age. The ontogeny of the visual cortex involves many morphogenetic changes and this study will help in determining and confirming the various developmental criteria of the rat primary visual cortex.